How Young Mothers Rely on Kin Networks and Formal Childcare to Avoid Becoming NEET in the Netherlands - Dicks, Alexander; Levels, Mark; van der Velden, Rolf; Mills, Melinda C. (Frontiers in Sociology, 2022)
Motherhood is often cited as one of the main reasons for young women to become NEET (not in employment, education, or training). Given the potential long-term negative implications of NEET status, it is important to understand which types of resources can help young mothers to avoid becoming NEET around childbirth. In this paper we investigate how the chances of young mothers to become and stay NEET around the time of first birth are related to the availability and characteristics of members of their social support network, especially partners and grandparents, to assist in childcare. In addition, we consider the local availability of formal childcare. We use population-wide register data from the Netherlands and estimate discrete-time event-history models. Our results show that young mothers who are cohabitating or married are less likely to become NEETs than single mothers. We also show that economic activity and relative wage of both young mothers and their partners decreases the likelihood to become NEET and to exit NEET. With respect to the grandparents, we find that having more grandparents live in the immediate vicinity is associated with a lower likelihood to become NEET and a higher likelihood to exit NEET. Furthermore, we find that young mothers with economically inactive parents are more likely to become and less likely to exit NEET. Lastly, we find evidence for crowding-out of informal and formal childcare. Formal and informal childcare sources interact in such a way that the role of either becomes less important as more of the other is available.